Development and Performance Evaluation of a Conveyor Belt Type Animal Treadmill - Singh, R C; Srivastava, NSL (Journal of Agricultural Engineering, 2006)
A portable conveyor belt type animal treadmill has been designed and developed at CIAE, Bhopal for laboratory studies on work performance and fatigue of draught animals. The treadmill consists of a portable frame, conveyor belt, railings, advance variable speed control system, transport cum inclination changing wheels, a loading device for animal with suitable harnessing system and inclined platforms to help the test animal to climb up for the experiment. The speed of conveyor belt can be adjusted in the range of 0 - 2.5 km/h and draft load on the animals can be exerted from 0 -15% of body weight. The treadmill was tested for its performance with Malvi breed of bullocks on draft loads equivalent to 6, 6.5, 7 and 7.5 % body weight of bullock at belt speed of 1.6, 1.8,2.1 and 2.24 km/h. The power requirement to operate the treadmill ranged from 1.1 to 2.70 kW at belt speed of 0.5 to 2.5 km/h with and without load respectively.